Genetics of a male-sterile rye of 'G-type' with results of the first F1 –hybrids. - Gi., Melz; Melz, Gu.; Hartmann, F. (Plant Breeding and Seed Science, 2003)
Male-sterile plants of G-type were found in rye cv. Schlagler alt. The major recessive gene controlling this male-sterility is allelic with male-sterility genes of the C- and R-types. The genetic system of the Pampa-type is completely different; it is controlled by dominant gene(s) and mt-DNA showed different restriction fragment patterns. The major gene of G-type msl(Rfgl) is located on chromosome arm 4RL; the sites of the minor genes ms2 and ms3 were found on chromosomes 3R and 6R. Hybrids produced by crossing malesteriles of G-type with inbred lines have normal pollination and, are therefore less sensitive to ergot, like population rye. In 2000 the mslnr-system of G-type rye was registered as "Guelzowerl". Male-sterile plants of "Guelzowerl" were used to produce the rye hybrid cultivar "Novus", which was also registered in 2000. "Novus" is the first rye hybrid cultivar with resistance to powdery mildew.